PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN PENDEKATAN KONTEKSTUAL - Asmaun Sahlan (Fak. Tarbiyah UIN Maliki Malang, 2011)
This article aims to review the teaching of Islamic religious education with a contextual approach. Learning Islamic education sometimes is not fun for the students, because learning methods monotonous and unpleasant. Then one model of learning is the learning of Islamic religious education with a contextual approach. Contextual learning methods can offer a new concept of Islamic religious education learning fun. Islamic religious education lesson with a contextual approach involves seven main components of effective learning: constructivism, inquiry, questioning, learning community, and reflection. Islamic religious education lesson with a contextual approach to its application in everyday life can be done through various methods, namely: making meaningful connections, doing significant, self-regulated learning, collaborating, critical and creative thinking.